The culture of contentment - Galbraith, John Kenneth, 1908-2006. (Boston : Houghton Mifflin Co., 1992)
This book traces the course of America's current sense of contentment, stemming from the economic comfort achieved by the fortunate, politically dominant community during the Reagan-Bush era of the 1980s. Galbraith focuses on the results of this stasis, including short-term thinking and investment, government as a burden, and corporate sclerosis. The author also explores international issues, such as the parallels between the denial of trouble in Eastern Europe and problems unrecognized in America. This book is a groundbreaking assessment of the future of America.
Includes index: p. 185-195.
Keywords: Poor -- United States; Free enterprise -- United States; Social values; United States -- Economic policy -- 1981-1993.; United States -- Economic conditions -- 1981-2001.; United States -- Social conditions -- 1980-2020.; United States -- Foreign relations -- 1981-1989.; United States -- Foreign relations -- 1989-1993.